Development of a microcontroller-based gas detection system using wireless sensor network - AL-Amri, Mohammed Amer Omar; Razali, Muda (2021)
The development of the equipment and our daily life is the major failures to protect the environment against pollution. Consequently, the ecological contamination control and monitoring systems become a major issue. The liquefied petroleum (LPG) and its leakage in large amounts cause explosive accidents. Therefore, gas leakage detection and alerting are of prime importance. Gas leakage detection and alert systems are of extreme importance in homes, industries, automobiles, etc. Besides, the survivability of human life and its effects relies upon the early discovery of gas leakage. Therefore, in the area of wireless sensor networks and earlier gas detection (alert system) is imperative. The monitoring, reorganization, and controlling of the data are the key concern of Wireless Sensor Network.